Consideraciones sobre la formación y transformación de la identidad de atletas profesionales de fútbol en Brasil (2010)
The article is a contribution to the understanding the process of construction and transformation of professional identity of the soccer player in Brazil. Both athletes' good and bad outcomes in the search of professional recognition are our path to the road of that analysis and scrutiny. Grounded in Habermas theory, we scrutinize sports - soccer in particular - as a social sector overrun by the systemic order and ruled by money and power. Since soccer, as the sport of crowds has been colonized by the "instrumental reason", it has been fueled by strong marketing appeal and as such brings about the world of life (culture, society and identity) as well as the twisted dreams and expectations of thousands of individuals and of their families. Accordingly, the life stories and examples brought about by this text hint at the intertwined relationships between the world of soccer, the dreams of a successful career, the actual possibility of failure and the construction of psychosocial identities within that "surprise box" which soccer seems to be.